Association between increased C-reactive protein and cardiovascular disease among patients with rectal cancer - Huimin Qiao; Huimin Qiao; Changxin Wang; Chunhong Yang; Lei Lei; Lei Lei; Yijing Chen; Yijing Chen; Yun Luo; Xiangfu Zeng; You Guo (Frontiers in Oncology, 2023)
PurposeThis study aimed to investigate the association between increased C-reactive protein (CRP) and cardiovascular disease (CVD) in individuals with rectal cancer, as well as to understand the effect of chemotherapy for cancer on increasing CRP and its underlying mechanisms.Patients and methodsFrom January 1, 2010 to December 31, 2020, individuals with rectal cancer were evaluated at the First Affiliated Hospital of Gannan Medical University. Then, in patients with rectal cancer, the relationship between increased CRP and CVD attributes was summarized, and the impact of chemotherapy on CRP levels was qualitatively assessed. For further investigation into potential regulatory mechanisms of CRP, differentially expressed genes (DEGs), GO and KEGG enrichment analyses were conducted.ResultsA total of 827 individuals were included in the study, including 175 with CVD (21.16%) and 652 without CVD. A significant association between increased CRP and CVD events was observed in rectal cancer patients (p < 0.01), and it significantly improved the classification performance of the CVD predictive model in the AUC (0.724 vs 0.707) and NRI (0.069, 95% CI 0.05-0.14). Furthermore, a comparison of CRP levels before and after chemotherapy revealed a significant increase among rectal cancers post-treatment (p < 0.001). Analysis of differentially expressed genes and co-expression indicated that 96 DEGs were involved in the pathophysiology of increased CRP after chemotherapy, and three hub genes were implicated in atherosclerotic susceptibility.ConclusionIn conclusion, our findings indicated that increased CRP levels following chemotherapy profoundly impacted CVD events in individuals with rectal cancer, and may be beneficial in promoting CVD prediction in clinical practice.